Rice (Oryza sativa) research in India - KRISHNAIAH, K (The Indian Journal of Agricultural Sciences, 2013)
In rice (Oryza sativa L) varietal improvement had been largely through pureline selection before fifties. Intervarietal hybridization programme was the first serious attempt to break the yield barrier in tropical rice. A breakthrough in breeding was witnessed with the concept of semi-dwarf, non-lodging plant type. Special breeding programmes were also launched to develop varieties, suited to rainfed uplands, shallow lowlands, semi-deep and deep water areas as well as problem soils. The All-India Co-ordiriated Rice Improvement Project played a key role in rapid material generation and varietal identification suitable forÂ·varied situations. The mechanism of inter-discipline-based multi location testing facilitated development ofagro-ecology-specific varietal and matching production technology. This model has helped to evolve more than 528 high-yielding, dwarf rice varieties and enabled us to achieve a record production of 82 million tonnes of milled rice during 1994-95, ensuring self-sufficiency in rice. Eleven rice hybrids have been released so far for commercial cultivation. The fine grain and aromatic rice helped increase rice export. India exported 5.5 million tonnes rice valued at Rs 30 000 million. The article deals with the present rice scenario in India.